2012
DOI: 10.1002/cmdc.201200014
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonimidamides as Sulfonamides Bioisosteres: Rational Evaluation through Synthetic, in Vitro, and in Vivo Studies with γ‐Secretase Inhibitors

Abstract: Although not endogenous in nature, the sulfonamide functionality is widely found in organic molecules with biological activity. A search of Thomson Reuters Integrity reveals that the sulfonamide motif appears in 111 approved drugs or agents in clinical trials, [1] and the total number of organic molecules containing this functional group is enormous. In contrast, the sulfonamide isostere [2] in which one of the sulfonamide oxygen atoms have been replaced by a nitrogen atom, thus creating a sulfonimidamide ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 22 publications
0
65
0
Order By: Relevance
“…Sulfonimidamide is an isostere of sulphonamide, which is formed by replacing one of the O-atoms by nitrogen of sulfonamide. The title compound can be considered as a potential pecursor for the preparation of sulfonimidamids [9][10][11][12]. However crystal structures of sulfinylcarbamate derivatives are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfonimidamide is an isostere of sulphonamide, which is formed by replacing one of the O-atoms by nitrogen of sulfonamide. The title compound can be considered as a potential pecursor for the preparation of sulfonimidamids [9][10][11][12]. However crystal structures of sulfinylcarbamate derivatives are rare.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized, open-label clinical trial of tasisulam sodium versus paclitaxel as second-line treatment in patients with metastatic melanoma has recently been stopped early because of safety issues in the tasisulam arm. Although it was considered to be unlikely that tasisulam was superior to prior chemotherapies, the importance of pharmacokinetic monitoring of compounds with complex dosing was underscored [43]. …”
Section: Discussionmentioning
confidence: 99%
“…1). For example, Sehgelmeble et al [43] found significant potencies when profiling sulfonimidamide-based analogs of sulfonamidic γ-secretase inhibitors. Furthermore, N-acylated sulfonimidamides were shown to have bioisosteric properties to carboxylic acid [44,45,46,47,48,49].…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] Sulfonimidamide derivatives were recently evaluated as sulfonamide bioisosteres in γ-secretase inhibitors [11,15] and showed increased solubility, decreased lipophilicity and decreased plasma protein binding in relation to their sulfonamide-containing analogues. [11] Moreover, cyclic sulfonimidamides have been identified as potential carboxylic acid bioisosteres, on the basis of promising physicochemical properties. [16] In line with this, our group recently found complementary results for linear acyl-substituted sulfonimidamides of types III and IV.…”
Section: Introductionmentioning
confidence: 99%
“…[1,5] Moreover, this functionality serves as a precursor in the preparation of sulfonimidamides (II) [6][7][8][9][10][11][12] and acyl-sulfonimidamides (III and IV). [13,14] Sulfonimidamide derivatives were recently evaluated as sulfonamide bioisosteres in γ-secretase inhibitors [11,15] and showed increased solubility, decreased lipophilicity and decreased plasma protein binding in relation to their sulfonamide-containing analogues. [11] Moreover, cyclic sulfonimidamides have been identified as potential carboxylic acid bioisosteres, on the basis of promising physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%